EVALUATION OF EFFECTIVENESS OF CHITOSAN HYDROGEL AS HAEMOSTATIC FROM DORSAL NASAL VEINS IN RABBITS - Bassim K.Khashjoori; Abdalbari A. Alfars (Basrah Journal of Veterinary Research)
The haemostatic capability, adhesion ability and biocompatibility of chitosan sponges was compared with conventional method as control group. The chitosan sponges were briefly immersed in an aqueous 20% ammonia solution before being applied to a rabbit dorsal nasal vein wound. The total amount of bleeding from the injured veins until hemostasis was similar for both chitosan and control group. The complete hemostasis success rates for both the chitosan and control group were also similar. Under hemostasis, the chitosan sponges strongly adhered to the surface of the rabbit muscles, whereas the control group. Under wet conditions, however, there was no significant difference in the adhesive ability between the two groups. During implantation, the chitosan sponges were much more flexible and resistant to breakage that good. The biocompatibilities in addition, biodegradation rates of the Chitosan sponges were very different after subcutaneous implantation in rabbit.